Manajemen Sekolah Berbasis Makayaklo (Studi Kasus MTs Swasta Muhammadiyah Matsa Halmahera Selatan) - Irfandi R. Hi Mustafa; Fahrun Yamin; Iswadi M. Ahmad (Academy of Social Science and Global Citizenship Journal, 2026)
This study aims to describe and analyze the local wisdom values ​​of Makayaklo culture in the Makian community and examine its implementation as a pillar of school management at MTs Swasta Muhammadiyah Matsa, South Halmahera Regency, North Maluku. Makayaklo is a kinship-based mutual cooperation philosophy that emphasizes collective cooperation, moral responsibility, and deliberation. Using a qualitative approach with a case study method, this study collected data through in-depth interviews, participant observation, and documentation. The results show that Makayaklo values ​​are internalized in four pillars of school management: participatory planning (weekly deliberation), solidarity-based organizing, program implementation through collective community service, and social trust-based supervision. In conclusion, Makayaklo culture has proven effective as a social glue as well as a management strategy that is adaptive to the local context.    Keywords: Makayaklo Culture, Makian Tribe, School Management.